Time-resolved and excitation-dependent photoluminescence study of CdTe/MgCdTe double heterostructures grown by molecular beam epitaxy - Zhao, Xin-Hao; DiNezza, Michael J.; Liu, Shi; Lin, Su; Zhao, Yuan; Zhang, Yong-Hang (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2014)
This Letter reports the optical properties of CdTe/MgCdTe double heterostructures grown by molecular beam epitaxy. Low-temperature photoluminescence shows strong band-to-band emission and very weak defect related peaks, indicating low defect densities. The measured Shockley–Read–Hall lifetimes range from 57 to 86 ns at room temperature for samples grown under different conditions. The material radiative recombination coefficient B in the recombination rate defined as R = A Δ n + ( 1 − γ ) B Δ n 2 + C Δ n 3 [Wang et al., Phys. Status Solidi B 244, 2740 (2007)] is evaluated to be 4.3 ± 0.5 × 10−9 cm3·s−1 with a photon recycling factor γ of 0.85 calculated based on the geometric structure of the samples.